2009
DOI: 10.1007/s10689-009-9273-5
|View full text |Cite
|
Sign up to set email alerts
|

Are prediction models for Lynch syndrome valid for probands with endometrial cancer?

Abstract: Currently, three prediction models are used to predict a patient's risk of having Lynch syndrome (LS). These models have been validated in probands with colorectal cancer (CRC), but not in probands presenting with endometrial cancer (EMC). Thus, the aim was to determine the performance of these prediction models in women with LS presenting with EMC. Probands with EMC and LS were identified. Personal and family history was entered into three prediction models, PREMM(1,2), MMRpro, and MMRpredict. Probabilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The only other study looking at LS prediction models among EC cases examined the sensitivity of PREMM 1,2 , MMRpredict, and MMRpro in 13 population-based EC cases with LS and showed that these models performed reasonably well in EC cases, with sensitivities ranging from 64 to 100%. 24 Our larger analysis supports the high yield in sensitivity but also reveals that the predictive models tend to assign greater weight to a diagnosis of EC compared with CRC (e.g., just the presence of an EC diagnosis in a proband results in a PREMM 1,2,6 score above the 5% cut-off point).…”
Section: Discussionsupporting
confidence: 68%
“…The only other study looking at LS prediction models among EC cases examined the sensitivity of PREMM 1,2 , MMRpredict, and MMRpro in 13 population-based EC cases with LS and showed that these models performed reasonably well in EC cases, with sensitivities ranging from 64 to 100%. 24 Our larger analysis supports the high yield in sensitivity but also reveals that the predictive models tend to assign greater weight to a diagnosis of EC compared with CRC (e.g., just the presence of an EC diagnosis in a proband results in a PREMM 1,2,6 score above the 5% cut-off point).…”
Section: Discussionsupporting
confidence: 68%
“…Cancer family risk (our categories or PREMM 1,2,6 scores) did not reliably predict germline mutation, and several mutation carriers had no history of LACs in relatives ( Table 4 ), confirming reports that family history fails to identify Lynch carriers. 30 33 As noted, some women with a previous history of cancer were excluded from the GOG210 study.…”
Section: Discussionmentioning
confidence: 99%
“…There are newer clinical prediction tools, such as PREMM5, MMRpredict, and MMRpro, mostly developed using the colorectal cancer population; unfortunately, these tools have limited clinical utility for gynecological malignancies 20–22. These prediction tools have lower discriminative ability to distinguish mutation carriers from non-carriers in endometrial cancer, and no such tools exist in ovarian cancer 21 23. More importantly, these tools take time, and rely on detailed and accurate history taking, which is often impractical in busy clinical settings.…”
Section: Discussionmentioning
confidence: 99%